The Effect of CPR Training With Real-Time Feedback on Compression Depth Among Health Care Professionals: A Critically Appraised Topic - Jessica J. Heyburn; Ryan T. Tierney; Jamie L. Mansell; Anne C. Russ (International Journal of Athletic Therapy and Training, 2026)
Clinical Question : Among health care professionals, does CPR training and performance with real-time feedback improve adherence to guideline-recommended compression depth compared with standard CPR training and delivery methods? Clinical Bottom Line : CPR training and performance using real-time feedback devices help health care providers achieve compression depths that more closely follow current guidelines, compared with standard training without feedback devices. In four randomized controlled trials, feedback delivered through audiovisual or smartwatch devices consistently increased both the percentage of compressions within the correct depth range and the overall average depth. Instructor-only feedback showed smaller, nonsignificant improvements, suggesting that the type of feedback devices and timing play a key role in their effectiveness.